The place of syllogistic in logical theory - Clark, Michael (Nottingham University Press, 1980)
Chapter 1 presents BS, a basic syllogistic system based on Aristotle's logic, in natural deduction form. Chapters 2 and 3 treat the metatheory of BS: consitency, soundness, independence, and completeness. (We show how Aristotle's attempt to show his logic was complete anticipates modern Henkin-style completeness proofs.) Chapter 4 and 5 deal with syllogistic and, in turn, propositional and predicate logic, chapter 6 is on existential import, chapter 7 on subject and predicate and chapter 8 on classes. Chapter 9 adds negative variables to BS, and proves its soundness and completeness.